นโยบายรัฐบาลและการปฏิบัติต่อแรงงานข้ามชาติตามพระราชบัญญัติเงินทดแทน พ.ศ. 2537 - พศกร โยธินนีรนาท (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This study aims to study 3 aspects which are policy, workforce protection, and related problems and obstacles. The data was collected by an in-depth study of laws and government-related regulations and the interview of the 4 key informant workforce officers and 11 migrant labours that were impacted by this issue. The findings revealed that there was no correlation in setting the workmen’s compensation policy between national-level sector and organization-level sector. As a result, problems in managing the migrant labour’s compensation occurred with migrant labour of the 3 countries which are Myanmar, Cambodia, and Laos. Secondly, the workforce protection process that indicates the necessity that workers getting injuries from a workplace need to be compensated have been the contrary. Regarding the Workmen’s Compensation Act B.E. 2537 that the Social Security Office (SSO) abides, which focuses on the equality and equity of the people, some of the migrant labours did not received the compensation. Lastly, problems, obstacles and limitations with the policy (รส 0711/ว751), the findings showed that there were some complications in the compensation payment process due to the misinterpretation of the Social Security Office (SSO). While the workforce protection laws did not indicate the need of presenting certain documents from the migrant labours, the Social Security Office (SSO) did ask to see them. This has led to problems in accessing compensation fund which will affect the image of the country in regard to the violation of labours’ human rights.